Performance of Full‐Scale Enhanced Reductive Dechlorination in Clay Till. Issue 1 (9th July 2012) - Damgaard, Ida; Bjerg, Poul L.; Jacobsen, Carsten S; Tsitonaki, Aikaterini; Kerrn‐Jespersen, Henriette; Broholm, Mette M.
<x xml:space="preserve">Abstract</x> At a low permeability clay till site contaminated with chlorinated ethenes (Gl. Kongevej, Denmark), enhanced reductive dechlorination (ERD) was applied by direct push injection of molasses and dechlorinating bacteria. The performance was investigated by long‐term groundwater monitoring, and after 4 years of remediation, the development of degradation in the clay till matrix was investigated by high‐resolution subsampling of intact cores. The formation of degradation products, the presence of specific degraders Dehalococcoides spp. with the vinyl chloride (VC) reductase gene vcrA, and the isotope fractionation of trichloroethene, cis‐dichloroethene (cis‐DCE), and VC showed that degradation of chlorinated ethenes occurred in the clay till matrix as well as in sand lenses, sand stringers, and fractures. Bioactive sections of up to 1.8 m had developed in the clay till matrix, but sections, where degradation was restricted to narrow zones around sand lenses and stringers, were also observed. After 4 years of remediation, an average mass reduction of 24% was estimated. Comparison of the results with model simulation scenarios indicate that a mass reduction of 85% can be obtained within approximately 50 years without further increase in the narrow reaction zones if no donor limitations occur at the site. Long‐term monitoring of the concentration of chlorinated ethenes in the underlying chalk aquifer revealed that the aquifer was affected by the more mobile degradation products cis‐DCE and VC generated during the remediation by ERD.